Personal internet of things networks: An overview of 3GPP architecture, applications, key technologies, and future trends - Fariha Eusufzai; Aldrin Nippon Bobby; Farzana Shabnam; Saifur Rahman Sabuj (International Journal of Intelligent Networks)
The use of the personal Internet of Things (PIoT) is rapidly expanding across a range of application areas. It is needed for real-time monitoring, wireless coverage, remote sensing, delivery, security, surveillance, and civil infrastructure inspection. Smart PIoT devices provide new opportunities in wearable, public, and home automation, making them the next significant development in PIoT technology. The study provides a comprehensive overview of PIoT systems, including their architecture, applications, technology, and future developments. This paper begins with a comprehensive overview of prior research about the PIoT network. Then, we present an overview of PIoT classification and a comprehensive explanation of the PIoT architecture. We also investigate the requirements and technology of the PIoT network. Additionally, we provide a thorough examination of several applications for PIoT networks. Moreover, we emphasize some significant challenges and ongoing problems confronting the PIoT network. Finally, we address recent research trends and outline potential future study directions.